The fish diversity in the upper reaches of the Salween River, Nujiang River, revealed by DNA barcoding - Chen, Weitao (Sci Rep, 2015)
Nujiang River (NR), an essential component of the biodiversity hotspot of the Mountains of Southwest China, possesses a characteristic fish fauna and contains endemic species. Although previous studies on fish diversity in the NR have primarily consisted of listings of the fish species observed during field collections, in our study, we DNA-barcoded 1139 specimens belonging to 46 morphologically distinct fish species distributed throughout the NR basin by employing multiple analytical approaches. According to our analyses, DNA barcoding is an efficient method for the identification of fish by the presence of barcode gaps. However, three invasive species are characterized by deep conspecific divergences, generating multiple lineages and Operational Taxonomic Units (OTUs), implying the possibility of cryptic species. At the other end of the spectrum, ten species (from three genera) that are characterized by an overlap between their intra- and interspecific genetic distances form a single genetic cluster and share haplotypes. The neighbor-joining phenogram, Barcode Index Numbers (BINs) and Automatic Barcode Gap Discovery (ABGD) identified 43 putative species, while the General Mixed Yule-coalescence (GMYC) identified five more OTUs. Thus, our study established a reliable DNA barcode reference library for the fish in the NR and sheds new light on the local fish diversity.